DEVELOPMENT OF ROLE PLAY METHOD TO IMPROVE THE ABILITY OF SPEAKING ARABIC IN ISLAMIC ELEMENTARY SCHOOL - Nurul Makrifah (Sekolah Tinggi Ilmu Tarbiyah Al - Ibrohimy Bangkalan, 2023)
Speaking Arabic is very important to be mastered by students considering the importance of Arabic as the language of the Quran. However, in reality at Madrasah Ibtidaiyah, students are not proficient in speaking Arabic. One of the factors is that the method used does not encourage speaking skills (takallam), therefore, it is necessary to develop an Arabic language method to improve speaking skills in MI students.This study aims to produce a design Arabic language method to improve speaking skills, describe the implementation of the Arabic role play method that has been developed to improve speaking skills, describe the effectiveness of developing Arabic language methods to improve speaking skills.This type of research is development research with reference to the ADDIE development model which consists of five stages, including the analyze, design, develop, implement, evaluate stages. The results of the study show that the design of the development of the Arabic roleplay method to improve speaking skills refers to the ADDIE development model, and is based on the principles of method development which include accuracy of coverage and accuracy of content, completeness of components, presentation of appropriate language and illustrations. Implementation of the roleplay method was carried out in 4 meetings in a limited trial, and 6 meetings in a large trial. The development of the Arabic roleplay method to improve speaking skills was declared effective by increasing students' speaking skills in the psychomotor aspect with an average pretest score of 73, and post-test of 91, with an increase in N-Gain of 0.66 in the medium category. From the cognitive aspect, the results of the pretest showed an average score of 68.5, a mean post-test score of 85.75 with an increase in N-Gain of 0.54 in the medium category.